(untitled) (Bangladesh Journal of Microbiology, 2016)
Domains of unknown functions (DUFs) are a big set of protein families within the Pfam database that includes proteins of unknown function. In the absence of functional information, proteins are classified into different families based on conserved amino acid sequences and are potentially functionally important. In Pfam database, the numbers of families of DUFs are rapidly increasing and in current the fraction of DUF families had increased to about twenty two percent of all protein families. In this study we targeted DUF2726 member proteins which are mainly present in different bacterial species of Gamma-proteobacteria and have a particular domain organization. We analyzed the protein sequences of domain DUF2726 using different computational tools and databases. We found that this domain contains a nuclear localization signal peptide, which is conserved in Escherichia spp. and Shigella spp. It were also predicted that it has nucleic acid binding properties. Analyzing protein-protein interactions functional partners associated with DUF 2726 were revealed. Protein secondary structure, transmembrane helices structure were predicted. We have found that it has gene neighbourhood and co-occurrences with protein RepA and RepB. RepA and RepB are functionally associated with replication. RepA is a replication protein and RepB is a replication regulatory protein. Presence of a nucleic acid binding properties, a nuclear localization signal (NLS) signalling peptide, and possible interaction pattern with replication proteins, conjectures its possible role as a NLS like signalling peptide. Bangladesh J Microbiol, Volume 31, Number 1-2,June-Dec 2014, pp 53-58